Needs Assessment and Design of Trans Palu Bus Stops (Case Study: Corridor 2 and Corridor 4) - Raynaldi Dwi Syahputra; Taslim Bahar; Ratnasari Ramlan (PT Publikasiku Academic Solution, 2025)
The City of Palu has established a transportation policy by introducing Bus Trans Palu as a form of mass public transport. However, the implementation of this policy has not yet been fully supported by adequate supporting facilities, particularly bus stops and shelters. This study aims to assess the existing conditions, determine the number of halte needed, and identify suitable locations and shelter designs along Corridor 2 and Corridor 4. Based on a survey of 400 respondents, the average willingness-to-walk distance was found to be 200 meters. Using this data, the placement of shelters is determined at intervals of 400 meters. The identification of potential halte locations was carried out using the buffer analysis method. Additionally, the selection of halte locations and layout design refers to the classification of shelter types as specified in SK Dirjen Hubdat No. 271/HK.105/DRJD/96. The results of the study indicate that there are currently 2 existing shelters in Corridor 2 and 1 in Corridor 4, but none of them meet the minimum standard requirements. Based on the analysis of halte needs, Corridor 2 requires a total of 31 shelters, while Corridor 4 needs 71 shelters to optimally serve the public.